Estimation of Serum Copper, Manganese, Selenium, and Zinc in Hypothyroid Patients - Ali, Eham Amir; Abdul Hussein, Hussein Kadhem; Tahssen, Yildiz Hassan (Journal of the Faculty of Medicine Baghdad, 2008)
Background: Decreased thyroid hormone synthesis and low levels of circulating thyroid hormones result in clinical and biochemical changes in hypothyroidism. As deficiency of thyroid hormones causes many metabolic processes to slow down, therefore; the maintenance of optimal health requires an adequate supply of carbohydrates, proteins and lipids, and macronutrients, micronutrients, and trace elements. Objective: Study the effect of the changing in serum level of the trace elements; Zn, Cu, Mn, and Se in hypothyroid patient. Patients and Method: Thirty seven hypothyroid patients and fifteen normal healthy control persons were participated in this study. Serum zinc and copper were determined using flame atomic absorption spectrophotometer. While determination of manganese and selenium were done using flameless atomic absorption spectrophotometer. Results: Serum Zn and Se level were significantly decreased in hypothyroidism, while there was significant increase in serum Mn level as compared with control group. Furthermore there was no significant difference in serum Cu level between groups. Conclusion: the results of this study suggest that the metabolism of Zn, Mn, and Se is abnormal in hypothyroid patients.